Critical Analysis on the Intersection of Technology and Human Rights: Emerging Obstacles to Justice and Accountability" - Aslam, Humaira; Ahmed, Rana Zaheer-ud-din; Awan, Sidra (Annals of Human and Social Sciences, 2022)
This review examines the current issues surrounding the intersection of technology and human rights. The growing reliance on artificial intelligence (AI) in decision-making processes across various sectors such as criminal justice, employment, public services, and finance brings forth significant risks to human rights. The use of AI complicates and diminishes accountability for harmful outcomes, undermining established mechanisms for holding responsible parties answerable. Furthermore, technologies that were initially envisioned to enhance human rights fact-finding have now been weaponized by both state and non-state actors. These technologies are employed for citizen surveillance, tracking, and the dissemination of disinformation, eroding public trust in information sources. Effectively addressing these challenges necessitates ensuring that the development and implementation of new technologies adhere to and uphold human rights principles. Conventional differentiations between the public and private sectors must be re-evaluated to remain relevant in the face of interconnected state and corporate activities associated with technological advancements.